SAT0029 PATIENT-PHYSICIAN DISCORDANCE IN ASSESSMENT OF DISEASE ACTIVITY IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Brites, L.; Costa, F.; Dinis de Freitas, J.; Luis, M.; Prata, A. R.; Assunção, H.; Saraiva, L.; Sousa, M.; Cunha, A. R.; Da Silva, J. A. P.; Duarte, C.
Abstract : Background: In rheumatoid arthritis (RA), global disease activity is commonly assessed, from the patient's and the physician's perspective, through a 100mm VAS. Previous studies have commonly shown a considerable discrepancy between the patient's and physician's assessment. Objectives: This study aimed evaluating patient-physician discordance in the assessment of disease activity and to explore its determinants. Methods: Cross sectional study including RA patients (ACR/EULAR 2010 classification criteria), aged ≥ 18 years, followed in a single tertiary centre. Data were collected from the most recent evaluation including sociodemographic features, disease duration (years), disease activity (DAS 28 3V-PCR), tender and swollen joint count 0-28 (TJC and SJC), VAS-pain-patient, patient and physician global assessment (PGA and PhGA respectively), erythrocyte sedimentation rate (ESR), C-reactive protein (CPR), Health assessment questionnaire (HAQ) and EuroQol five-dimension scale (EQ5D). The discrepancy between patients and physicians (ΔPPhGA) was defined as PGA minus PhGA, and a difference > |20mm| was considered as "discordant". A descriptive analysis was performed and variables described as proportions or means (+/- SD), as adequate. Correlation between ΔPPhGA and other variables was assessed through Pearson's correlation and comparison between groups through t-test. Variables with p<0.05 or otherwise considered clinically relevant were included in multiple linear regression analysis to identify predictors for ΔPPhGA. A p≤0.05 was considered statistically significant. Results: In total, 467 patients with RA were included (81.2% female; mean age 63.9% ± 12.2 years). PGA and PhGA were discordant in 61.7% of the cases, the patient scoring higher than the physician in 95% of these cases. The proportion of concordance increased ( p < 0.01) when considering only patients in remission (DAS 28 3V <2.6), (Graph 1). ΔPPhGA was moderately correlated with VAS-pain-patient (r = 0.59) and weakly correlated with SJC (r = -0.12), HAQ (r= 0.27), EQ5D (r = -0.28) and age (r = 0.21); all p<0.01. In multivariate analysis, VAS-pain-patient (β 0.74, 95% CI 0.62-0.88, p=0.00) and TJC (β 0.16, 95% CI 0.45-0.48, p=0.02) remained associated with a higher ΔPPhGA. Conclusion: Our study confirmed that a significant discrepancy between patients and physicians in the assessment of global disease activity is frequent in clinical practice, probably due to valorization of different parameters. This was much less pronounced among patients in remission. Higher VAS-pain-patient and TJC were independent predictors of greater discrepancy between patients and physician's assessment. Disclosure of Interests: Luisa Brites: None declared, Flavio Costa: None declared, João Dinis de Freitas: None declared, Mariana Luis: None declared, Ana Rita Prata: None declared, Helena Assunção: None declared, LILIANA SARAIVA: None declared, Marlene Sousa: None declared, Ana Rita Cunha: None declared, José Antonio P. da Silva Grant/research support from: Pfizer, Abbvie, Consultant of: Pfizer, AbbVie, Roche, Lilly, Novartis, Catia Duarte: None declared